A Comparative Study of Conventional and Microwave-Assisted Synthesis of Quinoxaline 1,4-di-N-oxide N-acylhydrazones Derivatives Designed as Antitubercular Drug Candidates - dos Santos Fernandes, Guilherme Felipe [UNESP]; Moreno-Viguri, Elsa; Santivañez-Veliz, Mery; Paucar, Rocio; Chin, Chung Man [UNESP]; Pérez-Silanes, Silvia; dos Santos, Jean Leandro [UNESP] (Wiley, 2017)
Quinoxaline 1,4-di-N-oxide (QdNO) and N-acylhydrazone subunit are considered privileged scaffolds in medicinal chemistry because of its wide spectrum of biological activities, such as antibacterial, antitubercular, antiviral, anticancer, and antifungal. Beirut's reaction is the mostly commonly employed synthetic method to obtain QdNO; however, extended time, low yields, and byproduct formation are common features observed during the synthesis. Microwave-assisted organic synthesis (MW) has gained popularity as an effective way to speed up chemical reactions, increasing yields and selectivity of a variety of reactions. Therefore, in an effort to synthesize compounds with potential to tuberculosis treatment, we reported herein the use of MW as a tool to obtain new QdNO derivatives containing the N-acylhydrazone subunit. Four different synthetic routes were evaluated by using different benzofuroxan derivatives in the Beirut's reaction. The synthetic route D, which employed a dioxolan-benzofuroxan derivative, has shown to be the best condition to obtain the desired hybrid quinoxaline. MW drastically reduces the reaction time to obtain all compounds compared to conventional heating. For compound 13, for example, the use of MW instead of conventional heating was able to reduce the reaction time in 192-fold. In conclusion, the use of a benzofuroxan derivative without additional electrophilic sites besides N-oxide nitrogen and the employment of the microwave-assisted synthesis have proved to be the optimum condition to obtain quinoxaline 1,4-di-N-oxide N-acylhydrazone derivatives.